Idiosyncrasies of thermofluorimetric aptamer binding assays - Tulsi Ram Damase; Peter B Allen (BioTechniques, 2019)
To explore thermofluorimetric analysis (TFA) in detail, we compared two related aptamers. The first, LINN2, is a DNA aptamer previously selected against EGFR recombinant protein. In this work we selected a second aptamer, KM4, against EGFR-overexpressing A549 cells. The two aptamers were derived from the same pool and bind the same target but behave differently in TFA. Our results suggest four overall conclusions about TFA of aptamers: 1. Some aptamers show reduced fluorescence upon target binding suggesting that target-bound aptamer is not always fluorescent. 2. Many aptamers do not obey the intuitive assumptions that aptamer–target interactions stabilize a folded conformation. 3. TFA may be most appropriate for aptamers with significant double-stranded structure. 4. Kinetic effects may be significant and the order of operations in preparing samples should be carefully optimized.